2021
DOI: 10.1177/21582440211059168
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Effect of Phonological Awareness and/or Phonics Instruction on Word and Pseudo Word Reading of English as an L2

Abstract: Despite considerable efforts made to understand the impact that instructional interventions have upon L2 reading development, we still lack a clear picture of the influence that PA and phonics instruction has upon reading in English as an L2. A search of the research literature published from 1990 to 2019 yielded 45 articles with 46 studies containing 3,841 participants in total. Effect sizes were recorded for the effect of various PA and/or phonics instructional interventions on word and pseudo word reading. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…The effect size of NCSs was not reported independently and was instead included in the overall analysis. In addition, Murphy Odo (2021) conducted a review of 45 studies on EPA and phonics instruction for ELLs and found no significant differences in word reading effects between ELLs with a logographic background ( g = 0.43) and those with an alphabetic one ( g = 0.39). The effect size of pseudoword reading was larger for ELLs with a logographic background ( g = 0.82) than for those with an alphabetic one ( g = 0.52).…”
Section: Training In Developing English Language Learners’ Phonologic...mentioning
confidence: 99%
See 2 more Smart Citations
“…The effect size of NCSs was not reported independently and was instead included in the overall analysis. In addition, Murphy Odo (2021) conducted a review of 45 studies on EPA and phonics instruction for ELLs and found no significant differences in word reading effects between ELLs with a logographic background ( g = 0.43) and those with an alphabetic one ( g = 0.39). The effect size of pseudoword reading was larger for ELLs with a logographic background ( g = 0.82) than for those with an alphabetic one ( g = 0.52).…”
Section: Training In Developing English Language Learners’ Phonologic...mentioning
confidence: 99%
“…By separating these two measures, researchers can assess different aspects of reading ability that may relate to diverse skills or strategies. Recent review studies on ELLs have consistently found that phonologically based training programs have a greater impact on the ability to read pseudowords than real words (Huo & Wang, 2017; Murphy Odo, 2021). These findings imply that participants who receive EPA and phonics training may experience greater improvements in decoding skills, which are essential for deciphering unfamiliar words.…”
Section: Training In Developing English Language Learners’ Phonologic...mentioning
confidence: 99%
See 1 more Smart Citation
“…This includes the following kinds of evidence: linguistic analysis of the mapping of print to sound for representational units of various sizes, for example, letters and words (Kearns, 2020;Vousden et al, 2011); longitudinal and cross-sectional studies of both typically developing students and those with exceptionalities (Double et al, 2019;Hjetland et al, 2019;Knight et al, 2019;Mervis et al, 2022); instructional studies comparing the effects of teaching representational units of various sizes (Bruck & Treiman, 1992;Christensen & Bowey 2005;Levy & Lysynchuk, 1997Yeh & Connell, 2008; fine-grained, step-by-step analysis of the effect of teaching on learning (Byrne & Fielding-Barnsley, 1989); cross-sectional and longitudinal research examining connections between students' knowledge of grapheme-phoneme relationships and their ability to decode larger units of language (Ehri & Robbins, 1992;Law & Ghesquière, 2017;Rastle, 2019); experimental and quasi-experimental studies of the effects of particular programs (e.g., Bradley & Bryant, 1983;Savage et al, 2020); and meta-analyses integrating the results of multiple experiments and quasi-experiments (Ehri, Nunes, Stahl, & Willows, 2001;Murphy Odo, 2021). Nothing like this concord of multidisciplinary evidence supports initial reading instruction that is implicit, unsystematic, or focused on units other than grapheme-phoneme correspondences.…”
Section: Phonics Explicit and Systematicmentioning
confidence: 99%
“…In RTI, Tier 1 is comprised of whole-class instruction using evidence-based methods, designed to be effective both for typically developing students and for those with exceptionalities. The reason that phonemic awareness and phonics are appropriate for Tier 1 initial reading instruction is that previous research has demonstrated their effectiveness with a diversity of beginning readers, including average-achieving students learning to read in L1, students with dyslexia, students who are low-achieving, and students who are learning to read in L2 (Ehri, Nunes, Stahl, & Willows, 2001;Murphy Odo, 2021;Suggate, 2016).…”
Section: Introductionmentioning
confidence: 99%